Burning in - Juchau, Mireille (Giramondo Publishing Company, 2007)
This is a novel about mothers and daughters, about the way the hidden past plays itself out in the present, and the conflicts between professional commitment and the responsibilities of family life. The story is told by a young woman, Martine, who translates the emotional distance she senses in her mother, Lotte, a holocaust survivor, into a passion for photography. Martine leaves Sydney to live in New York, in order to further her career, and has a child of her own. One day, her daughter Ruby goes missing in Central Park, while in the care of a nanny. The disappearance of her daughter throws.